Automação do processo de modelamento e detalhamento de estruturas pré-moldadas de concreto armado via tecnologia CAD e programação orientada a objetos - Regina Celia Guedes Leite (2002)
This Master Dissertation presents the design and implementation of a CAD (Computer Aided Design) system for automation of some steps of the process of modeling and detailing of pre-molded concrete structures, based on solid modeling. This system is implemented using the Object Oriented Programming paradigm (OOP) with the C++ language, using AutoCAD 2002 as the graphical platform. The concepts of objects, entities, databases and events are applied in AutoCAD, using the ObjectARX library. The resulting system was named PREMOLD which is intended to work as a preand post-processor for the analysis and detailing of pre-molded concrete structures starting from the launching of the structural elements. The application was constructed using thefundamental features of another modeler named Modelador 3D for unifilar structural geometrical modeling based on elements such as nodes, bars and surfaces. This work was developed in two basic steps, which are described in this dissertation. The first step consisted of the study and reformulation of the Modelador 3D so that it could be used for this work. Studies about design directives and fundamental requirements for pre-molded concrete structures, the C++ language and OOP paradigms are then presented. Next, the necessary changes and reorganization of the application Modelador 3D to satisfy those fundamental, directives and paradigms are described. The second stepconsisted of the computational and conceptual definition of the application PREMOL as a solid modeler for pre-molded structures, designed for skeleton structural systems or for unifilar models. The structure of classes developed for the PREMOLD is then presented.Such a class structure was constructed to be the basis for new developments on structural modeling using solid elements defined by nodes, bars and plates. The application PREMOLD was constructed to allow new implementations, such as the inclusion of new functionalities for the existent classes and creation of new classes. The insertion of newcommands and functions will also be permitted. The CAD system PREMOLD is intended to be flexible and independent so that simple interfaces will allow the communication with CAE system (Computer Aided Engineering) as a pre-processor and with CAM systems (Computer Aided Manufacturing) as a post-processor. Those are thephases of the productive process for pre-molded concrete structure, which this research work propose to automate. Finally, the contributions of this work to other areas, the limitations of the resulting application at this point are discussed, with suggestions for future work.